The improvement of agronomic traits of chrysanthemum through additional lighting and flower faselife assessment in Hargobinangun, Sleman, DIY - Ari Wijayani; Tutut Wirawati; Wongsoyudo Wongsoyudo (Jurnal Agrivet, 2012)
Chrysanthemum cultivation in medium height plains is still facing obstacles where the agronomic properties are not as good as in the highlands. It is important to find cultivation techniques that can improve agronomic properties of chrysanthemum. The setting of additional lighting technique remains to be learned then applied at planting chrysanthemum plain medium. The research purpose is to determine the best additional length of radiation for the improvement of agronomic properties of chrysanthemum. In addition to determining the best chrysanthemum varieties to be developed in the medium height plain as Hargobinangun. The research has been conducted in Hargobinangun, Sleman in April-August 2011 in two stages. The first stage is to determine the length of the addition of irradiation to improve the agronomic properties of chrysanthemum, namely 2,3,4 and 5 hours in the evening starting at 22:00 pm. While the second stage is to look at various kinds of flower faselife varieties, namely Sakuntala, Snow white, Wastu kania, Shamrock, Puspita Nusantara, Padmabuana and Tirta ayuni. The results was showing that cultivation techniques with the addition of irradiation for 5 hours will improve agronomic traits such as chrysanthemum plant height, stem diameter, flower diameter, flower number and brightness of flower color ribbon. While the flower varieties that have good prospects to be developed in the plain medium Hargobinangun because it has a much longer period of flower freshness is Puspita Nusantara, Sakuntala and Snow White.Key words: chrysanthemum, additional lighting, faselife of flowers